2020
DOI: 10.3390/bs10010026
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal Acetaminophen and Potential Risk of Autism Spectrum Disorder among Males

Abstract: Some evidence from the literature suggests that postnatal acetaminophen exposure may be associated with increased risk of autism spectrum disorder (ASD). Using a data set obtained from a previous study that was derived from an Internet-based survey among parents on 1515 children from the US, an adjusted odds ratio (aOR) and gender-specific aORs for doses of postnatal acetaminophen provided before age two were calculated against the outcome of ASD. Separately, parental uncertainty on the number of doses of acet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 53 publications
1
9
0
Order By: Relevance
“…Interestingly, very recently, it has been demonstrated that post-natal use of acetaminophen before the age of two is associated with an increase in the risk of ASD in male children [ 28 ], further confirming our previous results.…”
Section: Acetaminophen Use May Increase the Risk For Asd Which Cousupporting
confidence: 91%
“…Interestingly, very recently, it has been demonstrated that post-natal use of acetaminophen before the age of two is associated with an increase in the risk of ASD in male children [ 28 ], further confirming our previous results.…”
Section: Acetaminophen Use May Increase the Risk For Asd Which Cousupporting
confidence: 91%
“…Paracetamol has been furthermore advocated for the pharmacological closure of a patent ductus arteriosus in very preterm infants, although its efficacy is not superior to oral ibuprofen [2,3]. Follow-up examinations of preterm infants at 2 and 5 years of age currently do not point to altered neurodevelopmental outcome following postnatal paracetamol administration [71][72][73], while analysis of data from a survey among parents on 1515 US children found an increased risk of ASD following postnatal paracetamol administration before age two in boys but not in girls [74]. As a matter of concern, none of the trials employing paracetamol for closure of a patent ductus arteriosus in preterm infants registered with www.clinicialtrials.gov list ADHD and ASD as secondary outcome.…”
Section: Postnatal Use Of Paracetamol In Term and Preterm Newborn Infantsmentioning
confidence: 99%
“…However, information on long‐term outcome of large cohorts of preterm infants exposed to paracetamol with the attempt to endorse early closure of the ductus arteriosus is lacking. Unfortunately, this is a matter of urgency since there are several reports linking paracetamol exposure during pregnancy or in the neonatal period with adverse outcomes including autism spectrum disorder, attention deficit hyperactivity disorder, lower IQ and language delay 10–20 …”
Section: Introductionmentioning
confidence: 99%